Work Engagement and Organizational Commitment as Predictors of Organizational Citizenship Behavior: Penelitian - Marhisar Simatupang; Maharsi Anindyajati; Yulisa Susanti; Winanti Siwi Respati; Siti Masitoh; Raden Yudhi Satria R. A (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Organizational Citizenship Behavior (OCB) is recognized as an important factor that enhances organizational effectiveness by encouraging employees to perform discretionary behaviors beyond their formal job responsibilities. Previous studies have demonstrated that work engagement and organizational commitment contribute to employees' willingness to exhibit OCB; however, empirical evidence remains limited in post-pandemic organizational settings. This study aimed to examine the influence of work engagement and organizational commitment on Organizational Citizenship Behavior among employees. A quantitative causal-comparative research design was employed involving 92 permanent employees selected through simple random sampling from a population of 125 employees. Data were collected using standardized psychological scales measuring Organizational Citizenship Behavior, Work Engagement, and Organizational Commitment. The collected data were analyzed using multiple linear regression after satisfying the assumptions of normality and linearity. The findings revealed that work engagement had a significant positive effect on Organizational Citizenship Behavior. Organizational commitment also significantly predicted Organizational Citizenship Behavior. Furthermore, the simultaneous analysis demonstrated that work engagement and organizational commitment jointly contributed significantly to Organizational Citizenship Behavior. These findings suggest that employees who demonstrate higher levels of work engagement and stronger organizational commitment are more likely to perform voluntary behaviors that support organizational effectiveness beyond their formal job requirements. The study highlights the importance of fostering employees' psychological attachment to both their work and organization through supportive human resource practices to encourage positive extra-role behaviors and improve organizational performance.